2021
DOI: 10.1016/j.isci.2021.102842
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ITK signaling for T cell-mediated diseases

Abstract: The focus of this review is to examine the role of ITK signaling in multiple diseases and investigate the clinical potential of ITK inhibition. The diseases and potential interventions reviewed include T cell-derived malignancies as well as other neoplastic diseases, allergic diseases such as asthma and atopic dermatitis, certain infectious diseases, several autoimmune disorders such as rheumatoid arthritis and psoriasis, and finally the use of ITK inhibition in both solid organ and bone marrow transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 104 publications
1
18
0
1
Order By: Relevance
“…CD8 T cells from TCF-1 cKO mice exhibited innate memory-like phenotype by upregulating CD122, CD44, and effector and central memory phenotypes in mature CD8 T cells critical for GVHD development [33,34]. We also uncovered that CD8 T cells from TCF-1 cKO mice significantly upregulated Eomes and T-bet, two downstream transcription factors which are known to be involved in GVL [28,[35][36][37]. The loss of TCF-1 also led to upregulation of NK cell type 2 receptor (NKG2D).…”
Section: Introductionmentioning
confidence: 69%
“…CD8 T cells from TCF-1 cKO mice exhibited innate memory-like phenotype by upregulating CD122, CD44, and effector and central memory phenotypes in mature CD8 T cells critical for GVHD development [33,34]. We also uncovered that CD8 T cells from TCF-1 cKO mice significantly upregulated Eomes and T-bet, two downstream transcription factors which are known to be involved in GVL [28,[35][36][37]. The loss of TCF-1 also led to upregulation of NK cell type 2 receptor (NKG2D).…”
Section: Introductionmentioning
confidence: 69%
“…During GVHD, host tissues are damaged by the activity of alloactivated T cells. To determine whether damage to target organs of GVHD (skin, liver, and small intestine) was altered by loss of TCF-7 in donor T cells, we collected organs from mice allotransplanted as described above (Beilhack et al ., 2005; Mammadli et al ., 2021a; Mammadli et al ., 2021d; Weeks et al ., 2021). At day 7 and day 21 post-transplant, we collected pieces of skin, small intestine, and liver from recipient BALB/c mice.…”
Section: Resultsmentioning
confidence: 99%
“…CD8 T cells from TCF-7 cKO mice exhibited innate memory-like phenotype by upregulating CD122, CD44, and effector and central memory phenotypes in mature CD8 T cells critical for GVHD development (Dutt et al, 2011; Huang et al, 2013). We also uncovered that CD8 T cells from TCF-7 cKO mice significantly upregulated Eomes and T-bet, two downstream transcription factors which are known to be involved in GVL (Mammadli et al ., 2021a; Weeks et al, 2021; Zhou et al, 2010). Our data demonstrated that naïve CD8 T cells from TCF-7 cKO mice upregulated NK cell type 2 receptor (NKG2D).…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by differences between alloactivation in vivo and TCR-mediated activation in vitro. Ki-67, a proliferation marker, was also altered by loss of TCF-7, suggesting that CD8 T cells from TCF-7 cKO mice may proliferate more compared to WT CD8 T cells [93]. We also con rmed that CD8 T cells from TCF-7 cKO mice cause less tissue damage to the target organs, and loss of TCF-7 alters chemokine receptor expression both pre-and post-transplant, which could explain why these cells cause less severe GVHD with increased survival of recipient mice [74].…”
Section: Cd8 T Cells [89]mentioning
confidence: 99%